Avaliação de técnicas de sensoriamento remoto no mapeamento da distribuição da espécie arbórea invasora ligustrum lucidum wt aiton no sul do bioma Mata Atlântica - Boldo, Elton Leonardo (Universidade do Vale do Rio dos Sinos, 2015)
Set techniques to accurately map the occurrence of invasive species facilitates the understanding of its occurrence, dominance and preferred habitats. Produce detailed maps with associated tools in a Geographic Information System - GIS can help and reduce working time to map and point out the decision-making with a view to preparing studies, dynamics of occurrence and governance control of invasive species. The main objective of the study is to map the spatial distribution of L. lucidum in the mountainous region in the south of the Atlantic Forest biome, at different spatial scales. Specifically intended to (i) evaluate mappings invasion spots obtained from multispectral satellite images of Geoeye (pixel 0,25m²) and Landsat 5 TM (pixel 900m²), as to the accuracy of classification, total área invaded , size and number of spots; and if applicable, (ii) determining the potential for occurrence in a wider area, from 5 Landsat TM images. It applied supervised classification techniques for land use and the occurrence of invasive species determined the NDVI, the classification of pixels by Spectral Angle Mapper Method (SAM) and the accuracy of the kappa index. The classification Geoeye image showed an occurrence of 239.60 ha and a kappa index of 0.86, where the highest occupied area corresponded to spots between 1 and 100 m². Already using Landsat 5TM images presented in their final classification of an área 219.06ha of occurrence of the species, and a kappa index of 0.74, where the highest occupied area corresponding to larger spots 15.000m². To assess the accuracy of the low spatial resolution image used to the control points of Geoeye image, getting a kappa index 0.38. By accurate model was generated a potential occurrence model for a region of 341km², obtaining an area of 16.379ha the species and occurrence of 9.74% of L. lucidum over forest areas. The species has confirmed and representative occurrence in the area and in short time can become a threat to the forest ecosystem of Serra Gaucha, reaching invasion percentages which do not lend its eradication. Due to occur on a large scale of L. lucidum as an intruder, the control can only be possible in the early stages of the process, being economically and ecologically feasible restrictive in advanced stages.
Keywords: Ligustrum lucidum; Sensoriamento remoto; Espécie exótica invasora; Remote sensing; Invasive alien species; ACCNPQ::Ciências Biológicas::Biologia Geral